2021
DOI: 10.1186/s40337-021-00473-x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among staff on specialized eating disorder units in Norway

Abstract: Objective Burnout is commonly associated with low workplace wellbeing. Patients with eating disorders are frequently referred to as a particularly challenging group to treat. It is therefore important to study healthcare providers´ workplace wellbeing in settings which treat eating disorders. The aims of the current study were to (a) measure burnout among healthcare providers working on specialized eating disorder units in Norway, and (b) explore factors predicting burnout. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Likewise, Verhavert et al reported that dietary behavior was positively associated with the risk of burnout syndrome generating in people the consumption of fast food and unhealthy food [68]. This finding could be explained by the fact that military personnel are under constant pressures and desires to optimize performance in their service and pressures to meet certain objectives with traits of compulsiveness and perfectionism, leading to burnout and generating eating disorders [69,70].…”
Section: Factors Associated With Eating Disorder Symptomsmentioning
confidence: 99%
“…Likewise, Verhavert et al reported that dietary behavior was positively associated with the risk of burnout syndrome generating in people the consumption of fast food and unhealthy food [68]. This finding could be explained by the fact that military personnel are under constant pressures and desires to optimize performance in their service and pressures to meet certain objectives with traits of compulsiveness and perfectionism, leading to burnout and generating eating disorders [69,70].…”
Section: Factors Associated With Eating Disorder Symptomsmentioning
confidence: 99%